Amérique du Nord. - Dufour, A.-H. (Auguste-Henri), 1798-1865 (Armand Le Chevalier, 1871)
Map shows major cities, major roads, major railroads, state and territorial boundaries for the United States, ocean currents, shipping routes, and areas of Native American habitation; [modern day Alaska as] "Russie Americaine"; two [?] differing northwest boundary lines for Texas. Inset: "Carte supplémentaire des Iles N.E. de l'Amérique." Includes number of days for ocean travel from point to point. Relief shown by hachures and spot heights. Scale [ca. 1:12,334,000].